2015
DOI: 10.1002/cbin.10457
|View full text |Cite
|
Sign up to set email alerts
|

Biological characteristics of adipose tissue‐derived stem cells labeled with amine‐surface‐modified superparamagnetic iron oxide nanoparticles

Abstract: Cell labeling and tracking are becoming increasingly important areas within the field of stem cell transplantation. The ability to track the migration and distribution of implanted cells is critical to understanding the beneficial effects and mechanisms of stem cell therapy. The present study investigated the effects of amine-surface-modified superparamagnetic iron oxide (SPIO) nanoparticles on the biological properties of human adipose tissue-derived stem cells (hADSCs). Monodisperse hydrophobic magnetite (Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
3
11
0
Order By: Relevance
“…These results indicate that VSOPs-labelled hASCs can be expanded without affecting their viability and their ability to differentiate. This is consistent with the findings of others, who have not described any influence of IONPs on the differentiation capacity of different cell types, such as bone marrow-derived stem cells (BMSCs) [51,52], haNCSs [3] or ASCs [53].…”
Section: Discussionsupporting
confidence: 93%
“…These results indicate that VSOPs-labelled hASCs can be expanded without affecting their viability and their ability to differentiate. This is consistent with the findings of others, who have not described any influence of IONPs on the differentiation capacity of different cell types, such as bone marrow-derived stem cells (BMSCs) [51,52], haNCSs [3] or ASCs [53].…”
Section: Discussionsupporting
confidence: 93%
“…Meanwhile, we also found that the fluorescence intensity ascended with the increasing of concentration of MIRB, which was also indicated by intracellular iron content analysis. However, the intracellular iron content in 100  μ g/mL group did not reach 2-fold higher than that of 50  μ g/mL group, possibly due to limited cell uptake because of Fe saturation or Fe particle clumping at high MIRB concentration [8]. …”
Section: Discussionmentioning
confidence: 99%
“…Odonto-/osteogenic differentiation was measured to assess the effect of MIRB on the transdifferentiation potential of hDPSCs as previously described by Wang et al [8] using differentiation medium (Cyagen Biosciences Inc., Santa Clara, CA, USA). For osteogenic differentiation, hDPSCs were seeded at 3.1 × 10 3 cells/cm 2 and labeled by different concentrations of MIRB (12.5  μ g/mL, 25  μ g/mL, and 50  μ g/mL) and then allowed to reach 90% confluence.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The induction methods have been reported previously by our group (Wang et al, 2015). The induction methods have been reported previously by our group (Wang et al, 2015).…”
Section: Apoptosis and Cytotoxicity Assaymentioning
confidence: 93%